2017
DOI: 10.1002/2016jg003438
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a hierarchy of models reveals importance of substrate limitation for predicting carbon dioxide and methane exchange in restored wetlands

Abstract: Wetlands and flooded peatlands can sequester large amounts of carbon (C) and have high greenhouse gas mitigation potential. There is growing interest in financing wetland restoration using C markets; however, this requires careful accounting of both CO2 and CH4 exchange at the ecosystem scale. Here we present a new model, the PEPRMT model (Peatland Ecosystem Photosynthesis Respiration and Methane Transport), which consists of a hierarchy of biogeochemical models designed to estimate CO2 and CH4 exchange in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 102 publications
2
43
0
Order By: Relevance
“…In such models the methane production typically depends on the available carbon pool development (Li et al, 2016;Oikawa et al, 2017;Raivonen et al, 2017;Tian et al, 2010;Walter & Heimann, 2000;Wania et al, 2010;Watts et al, 2013;Zhuang et al, 2004), in line with our findings. In such models the methane production typically depends on the available carbon pool development (Li et al, 2016;Oikawa et al, 2017;Raivonen et al, 2017;Tian et al, 2010;Walter & Heimann, 2000;Wania et al, 2010;Watts et al, 2013;Zhuang et al, 2004), in line with our findings.…”
Section: Relation Between Methane Emission and Carbon Dioxide Fluxessupporting
confidence: 91%
“…In such models the methane production typically depends on the available carbon pool development (Li et al, 2016;Oikawa et al, 2017;Raivonen et al, 2017;Tian et al, 2010;Walter & Heimann, 2000;Wania et al, 2010;Watts et al, 2013;Zhuang et al, 2004), in line with our findings. In such models the methane production typically depends on the available carbon pool development (Li et al, 2016;Oikawa et al, 2017;Raivonen et al, 2017;Tian et al, 2010;Walter & Heimann, 2000;Wania et al, 2010;Watts et al, 2013;Zhuang et al, 2004), in line with our findings.…”
Section: Relation Between Methane Emission and Carbon Dioxide Fluxessupporting
confidence: 91%
“…However, analyzing and interpreting continuous flux measurements can be challenging as carbon exchanges are complex, often involving nonlinear, asynchronous processes across diverse timescales that can be difficult to characterize using traditional statistical analysis (Sturtevant et al, ). Methods such as wavelet decomposition and information theory show promise for addressing these complexities by considering issues of scale, nonlinearity, and asynchrony directly (Sturtevant et al, ) and have been shown to improve accurate representation of carbon cycling in process models (Oikawa et al, ). Wavelets are a particular powerful technique to investigate scale in geophysical and ecological analysis (Cazelles et al, ; Torrence & Compo, ).…”
Section: Introductionmentioning
confidence: 99%
“…A thorough understanding of CH 4 flux drivers is essential to these programs because the magnitude of CH 4 emissions may determine if restored wetlands are a GHG source or sink (Knox et al., ). These emissions could affect funding of wetland restoration programs if financed through C markets alone (Oikawa, Jenerette, et al., ), though wetlands provide a number of relevant ecosystem services, such as nutrient retention, protection from storms and sea‐level rise, and habitat preservation for wildlife (Hansson, Brönmark, Anders Nilsson, & Åbjörnsson, ; Swain, Boughton, Bohlen, & Lollis, ; Zedler & Kercher, ).…”
Section: Introductionmentioning
confidence: 99%